How can mHealth applications that are developed in one area of the developing world be adapted for use in others?. (10th June 2016) - Eze, Emmanuel; Gleasure, Rob; Heavin, Ciara
Abstract: The quality of healthcare in developing countries remains a critical issue, due in part to the limited infrastructure and resources available. The development of mHealth systems has been proposed as a possible solution. These systems extend the reach of medical care into rural areas by integrating smartphones and other mobile devices. Yet it is not clear how mHealth solutions designed and tested for use in one developing region can be adapted for use in others. This research-in-progress study frames this problem using a sociomaterial/coping perspective. A case study is proposed to extend and refine this model.